Could Oil Sector Revenue Displace Manufactures Export? Evidence from Selected Oil-Rich African Countries - Chile, Nzeh, Innocent; Ogomegbunam, Okolie David; Ibekwe, Okolie, Jonathan (Asian Development Policy Review, 2022)
This study investigated if revenue from the oil sector displaced the export of manufactures in oil-rich African countries over the period from 2000 to 2020. Using the panel ARDL model, findings indicate that in the short run, oil rents had an insignificant positive impact on the export of manufactures for all countries sampled. However, in the long run, the impact was positive. The short run results for the individual countries revealed that oil rents improved the export of manufactures for Nigeria and Ghana, while the impact for Libya, Algeria and Gabon was adverse. The study therefore concludes that the displacement of the export of manufactures by the proceeds from oil occurred at country-specific levels in the selected oil-rich African countries. Consequently, the study suggests that rents from oil in these countries should be used to develop facilities that encourage the development of the manufacturing sector.